Pendekatan Biopsikososial dalam Memahami Kesehatan Mental: Tinjauan Literatur - Hermawati, Luluk; Prameswari, Yuda Nabella; Irawati, Nur Bebi Ulfah; Amelia, Rossa; Zulfa, Hilizza Awalina; Dwiyanti, Sophie (Lembaga Pengembangan Kinerja Dosen, 2026)
Mental health is a fundamental component of overall health that influences quality of life, productivity, and individuals’ social functioning. The development of mental disorders, such as depression and anxiety disorders, cannot be explained by a single factor; rather, it results from the interaction of multiple multidimensional determinants. This literature review aims to analyze the contribution of biological, psychological, and social factors to mental health based on current scientific evidence. This study employed a systematic narrative review approach. Literature searches were conducted in PubMed and Google Scholar databases using keywords related to mental health and biopsychosocial factors. The inclusion criteria comprised studies involving human populations published between 2015 and 2025 with observational, systematic review, or meta-analysis designs. Data were analyzed narratively to identify consistent patterns of findings. The results indicate that biological factors, such as genetic predisposition, neurotransmitter dysregulation, and medical comorbidities, increase vulnerability to mental disorders. Psychological factors, including coping strategies, emotion regulation, and exposure to stress and trauma, influence individuals’ psychological conditions. Social factors, such as social support, socioeconomic status, work or academic environment, and stigma, also play a significant role. In conclusion, mental health is the result of a dynamic interaction among biological, psychological, and social factors. Therefore, a comprehensive biopsychosocial approach is essential in promotive, preventive, and curative efforts.